The relationship of healthcare service quality and patient satisfaction on patient loyalty of outpatient clinics in private hospitals in Malaysia - Othman, Nur Amalia (2024)
This research study intends to examine the importance of patient satisfaction as a predictor of patient loyalty and the role of healthcare service quality in shaping patient perceptions, experiences and satisfaction. This study will analyze the factors affecting healthcare service quality, patient satisfaction and its relationships on patient loyalty in Outpatient Clinics in Private Hospitals.